2010
DOI: 10.3329/jhpn.v28i4.6043
|View full text |Cite
|
Sign up to set email alerts
|

Limited Access to Iodized Salt among the Poor and Disadvantaged in North 24 Parganas District of West Bengal, India

Abstract: Iodine deficiency is endemic in West Bengal as evident from earlier studies. This community-based, crosssectional descriptive study was conducted in North 24 Parganas district during August-November 2005 to assess the consumption of adequately-iodized salt and to ascertain the various factors that influence access to iodized salt. In total, 506 households selected using the multi-stage cluster-sampling technique and all 79 retail shops from where the study households buy salt were surveyed. The iodine content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 3 publications
0
2
1
Order By: Relevance
“…[ 10 11 ] Present study, similar to other studies done in various settings of West Bengal reveal a coverage of household consumption of iodized salt, that is still far from the target of 90%. [ 15 16 17 18 ] Contrary to other studies done in West Bengal and other states of India, where non iodized salt consumption constituted a significant proportion, the present study found no households consuming non iodized salt. [ 12 13 ] An improved access to iodized salt of this deprived and poor section of the community is evident from this study, which may be attributed to continued efforts under NIDDCP to provide iodized packet salt at affordable price and a stringent ban on sell of non-iodized loose salt; however the findings also hint that only 'access to iodized salt' is not sufficient to maintain a good level of iodization at consumption.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…[ 10 11 ] Present study, similar to other studies done in various settings of West Bengal reveal a coverage of household consumption of iodized salt, that is still far from the target of 90%. [ 15 16 17 18 ] Contrary to other studies done in West Bengal and other states of India, where non iodized salt consumption constituted a significant proportion, the present study found no households consuming non iodized salt. [ 12 13 ] An improved access to iodized salt of this deprived and poor section of the community is evident from this study, which may be attributed to continued efforts under NIDDCP to provide iodized packet salt at affordable price and a stringent ban on sell of non-iodized loose salt; however the findings also hint that only 'access to iodized salt' is not sufficient to maintain a good level of iodization at consumption.…”
Section: Discussioncontrasting
confidence: 93%
“…These findings are biologically plausible and corroborated by a similar study in North 24 Parganas, West Bengal where a greater proportion of households with practice of storing salt in the shelf were found to consume adequately iodized salt. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…This becomes another challenge, due to the wide and varied availability and accessibility of existing salts in the communities participating in the present study (e.g., garlic, onion, herbs, lemon, and smoked flavored salts). These flavored salts may have influenced the evolution of Costa Rica's culinary culture, which has become globalized [51], as evidenced in studies carried out in other latitudes [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…This is because households’ access to use iodized salt is commonly dependent on awareness, availability and price [ 31 ]. Households with high economic status can afford to purchase salt from appropriate sources which contains iodine compared to poor households [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%